Generalized granuloma annulare presenting as arcuate dermal erythema - Miličić, Vesna (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2010)
Generalized granuloma annulare (GGA) is an uncommon cutaneous disease of unknown origin, characterized by numerous flesh-colored to erythematous papules with or without annular configuration. Clinical associations of GGA with diabetes mellitus, thyroid diseases, malignancies, AIDS, and chronic hepatitis C virus infection have been reported. Therapy has been attempted with various modalities with moderate efficacy. We report a case of GGA presenting as arcuate dermal erythema with excellent therapeutic response to corticosteroid therapy (a short course of intramuscular corticosteroids, a prolonged low oral dose, and topical corticosteroids).
Keywords: dermatologija; kožne bolezni